We were there : voices of African American veterans from World War II to the war in Iraq - Latty, Yvonne; Tarver, Ron (2004)
A history of the contributions of African-American soldiers from World War II to the present notes the segregation of the army until the Korean War and honors more than two dozen veterans of distinction.
World War II -- Korea -- Vietnam -- Persian Gulf War -- War on terror.
Keywords: African American soldiers -- Biography; African American sailors -- Biography; African American veterans -- Biography; United States -- Armed Forces -- African Americans -- History -- 20th century; United States -- Armed Forces -- Biography; United States -- History, Military -- 20th century -- Sources